Effect of Alkali Compound on Morphology and Luminescence Intensity of Europium-doped Yttria - Astuti Astuti; Mikrajuddin Abdullah; Khairurrijal Khairurrijal (Institut Teknologi Bandung, 2009)
Luminescent particles of europium-doped yttria (Y2O3:Eu) have been synthesized by heating nitrous precursors in a solution of polyethylene glycol (PEG) matrix containing alkali compound (LiOH, NaCl, KCl, and CaCl2). High luminescence intensity at around 612 nm contributed by electron transitions in Eu3+(5D0 → 7F0, 5D0 → 7F1,5D0 → 7F2, and 5D0 → 7F3) were observed. The highest intensity was observed in samples prepared using Li compound, but he smallest particle size was observed in samples prepared using Ca compound. This approach is promising for production of submicrometer down to nanometer-sized Y2O3:Eu particles that have both small in particle sizes and high luminescence intensity which is potential for use in development of luminescence ink that can be adapted to the current ink jet printing technology.